2013
DOI: 10.1364/ao.52.005088
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of self-absorption effect on aluminum emission in the presence of different noble gases: comparison between thin and thick plasma emission

Abstract: Aluminum spectra in the noble gases of helium and argon at initial delay times after plasma formation are numerically calculated. Temporal behavior of plasma emissions up to 200 ns after laser irradiation is investigated. Plasma parameters are computed by coupling the thermal model of laser ablation, hydrodynamic of plasma expansion, and Saha-Eggert equations. A spectrum is constructed from the superposition of 13 strong lines of aluminum and several strong lines of ambient gases. Spectral radiations are super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 44 publications
3
19
0
Order By: Relevance
“…In the previous work of our group, it was shown that the aluminum spectral lines in argon ambient gas are exposed to more intense self-absorption than in helium noble gas at the mentioned experimental condition [74]. So, since our results on the influences of gas natures on the plasma [74,76], as well as for having smoother spectrum, the analysis in this paper is limited to Al samples in He noble gas.…”
Section: Self-absorption Effectmentioning
confidence: 88%
See 2 more Smart Citations
“…In the previous work of our group, it was shown that the aluminum spectral lines in argon ambient gas are exposed to more intense self-absorption than in helium noble gas at the mentioned experimental condition [74]. So, since our results on the influences of gas natures on the plasma [74,76], as well as for having smoother spectrum, the analysis in this paper is limited to Al samples in He noble gas.…”
Section: Self-absorption Effectmentioning
confidence: 88%
“…So, since our results on the influences of gas natures on the plasma [74,76], as well as for having smoother spectrum, the analysis in this paper is limited to Al samples in He noble gas. In addition, it should be noted that the details of the influences of the ambient gas natures at different pressure conditions are investigated in Refs.…”
Section: Self-absorption Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma Science and Technology -Progress in Physical States and Chemical Reactions Figure 12. Different schematics of nonhomogeneous thick plasmas [10,13,34].…”
Section: Inhomogeneous Plasmamentioning
confidence: 99%
“…Rezaei et al [34] studied the spectral emissions of an aluminum sample located in argon and helium noble gases at 1 atm pressure, by applying a numerical calculation. They computed the plasma parameters by coupling the thermal model of laser ablation, hydrodynamic of plasma expansion, and Saha-Eggert equations.…”
Section: Inhomogeneous Plasmamentioning
confidence: 99%